SISTEM APLIKASI PENGELOLAHAN DATA KOMPLAIN UNTUK MENGUKUR KUALITAS KINERJA UNIT PDE BERBASIS WEB DI RSUD - Teguh Pradana; Anggit Septa Yurika (Joutica, 2017)
Decision Support Systems (DSS) are interactive computer-based system, which helps decision-makers to use the data and models to solve unstructured problems. Decisions can be taken by right (time and objective) and can be accounted for if it is supported by a system without doing individual aspects of the decision itself as well as the context of the problems faced.Thus the authors will take advantage of the application system pengelolahan complaint of data to measure performance web-based EDI unit. This system which will bridge the gap between students and the concentration of the majors to be taken with the help of the head of the study program. Decision Support System for Determination of Concentration Programs are designed using the programming language PHP and Mysql data base. And system design using CMS as decision support in determining the concentration of the majors to be taken in studying at the Faculty of Economics, University of the Free Pasuruan. Students are no longer confused / scared wrong in taking decisions for determination majors is to be retrieved